2020
DOI: 10.3991/ijet.v15i17.14637
|View full text |Cite
|
Sign up to set email alerts
|

Trends in MOOCs Research: Analysis of Educational Technology Journals

Abstract: Massive open online courses (MOOCs) have received a great deal of interest from educational institutions and private enterprises. Hence, several empirical studies and reviews have been produced. They will be at the heart of the synthesis presented in this article, which reviews the research objects, the analytical frameworks mobilized and the methodologies adopted in the research produced specifically between January 2012 and January 2018. The trends were identified by a review of 36 selected peer reviewed jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Additionally, it was found that descriptive statistics as a quantitative research approach and content analysis as a qualitative research approach were generally used in the dissertations as the methods of data analysis. Although the "Thematic and discourse analysis" methods were seen to be used very little in this study, Abdelghani (2020) stated that "Thematic/Discourse analysis" is the most used analysis method after descriptive statistics in the studies they analyzed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, it was found that descriptive statistics as a quantitative research approach and content analysis as a qualitative research approach were generally used in the dissertations as the methods of data analysis. Although the "Thematic and discourse analysis" methods were seen to be used very little in this study, Abdelghani (2020) stated that "Thematic/Discourse analysis" is the most used analysis method after descriptive statistics in the studies they analyzed.…”
Section: Discussionmentioning
confidence: 93%
“…Kara Aydemir and Can (2019) also found that the mixed method was on the increase, especially in recent years. However, Küçük et al (2013), Göktaş et al (2012b), Asdaque & Rizvi (2019), and Abdelghani (2020) stated that quantitative research is used less. On the other hand, Anderson et al (2021) found that qualitative approaches were used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…We undertook to conduct the current review to address some notable gaps: There is a lack of up to date reviews of recent research on MOOCs [22], in particular there is a dearth of reviews that distinguish empirical studies based on primary data (human participants), and many studies as we have seen are unclear on the full details of their methodology followed. The main research question this study sought to address was to determine what impact empirical MOOC research is having and in which topic areas.…”
Section: Specialisation Of Mooc Research Reviewsmentioning
confidence: 99%
“…In e-learning, recommendation systems are progressing with the advancement of Machine Learning algorithms and Big Data techniques. For instance, learning analysis can be handled to predict learner performance within Moodle [13]. It is therefore of utmost importance to study the evolution of recommendation systems since their emergence.…”
Section: Introductionmentioning
confidence: 99%